HUBUNGAN KEPRIBADIAN BIG FIVE DENGAN PERILAKU BERKENDARA BERISIKO PENGENDARA MOTOR SISWA SMA - Fatmawiyati, Jati; Al Farizi, Reza Hanif; Chusniyah, Tutut (Flourishing Journal, 2022)
Abstract: This research aims to determine the role of personality on risky driving behavior of high school students. This study is important to do, because the attitude of the motorbike rider causes a lot of traffic accidents. Data collection using the risky driving behavior scale from Iversen (2004) which has been adapted into Indonesian by Alfazi (2018) consists of 24 items. All items are valid with a validity value of 0.309–0.778 and a reliability of 0.688. Personality instrument uses Extra-Short Big Five Iventory-2 by Soto and John (2017) which has been adapted by Tresnawaty and Izdihar (2020) which consists of 15 items. The validity shows a value of 0.318–0.47 with a reliability of 0.611. The sample is 119 students of SMAN 1 Ngunut Tulungagung, grades 10-12 who rode motorbikes and distributed questionnaires using google form. Data analysis using multiple regression, previously tested for normality, linearity, and heteroscedasticity. The results of hypothesis testing show that personality is a predictor of risky driving behavior. However, when viewed pertrait, only agreeableness and neuroticism significantly affect risky driving behavior. Meanwhile, openness to experience, conscientiousness and extraversion are not significant. Abstrak: Tujuan pelaksanaan penelitiaan ini yakni untuk mengetahui peran kepribadian terhadap perilaku berkendara yang beresiko siswa SMAN. Penelitian ini penting untuk dilakukan, karena sikap pengemudi motor mengakibatkan banyak terjadi kecelakaan lalu lintas. Pengambilan data menggunakan skala risk driving behavior dari Iversen (2004) yang telah diadaptasi kedalam bahhasa Indonesia oleh Alfazi (2018) terdiri dari 24 aitem. Semua aitem valid dengan nilai validitas 0.309–0.778 dan reliabilitas 0.688. Instrumen kepribadian menggunakan Extra-Short Big Five Iventory-2 oleh Soto dan John (2017) yang telah diadaptasi oleh Tresnawaty dan Izdihar (2020) yang terdiri dari 15 aitem. Uji validitas menunjukkan nilai 0.318–0.47 dengan reliabilitas sebasar 0.611. Sampel 119 siswa SMAN 1 Ngunut Tulungagung, kelas 10-12 yang mengendarai sepeda motor dan penyebaran kuesioner menggunakan google form. Analisis data menggunakan Spearman Brown, karena saat dilakukan uji normalitas data tidak normasl. Hasil uji hipotesis menunjukkan tingkat signifikansi dibawah 0.05 (0.04<0.05), maka ada hubungan positif antara perilaku berkendara beresiko dengan neuroticism dan agreeableness, sedangkan hubungan opennes to experience, conscientiousness dan extraversion dengan perilaku berkendara beresiko tidak signifikan